Preparation process of low-viscosity high-fluidity ultra-high performance concrete
The preparation process for ultra-high performance concrete uses a polycarboxylic acid water reducer and silane coupling agent to reduce viscosity and enhance fluidity, while the hydrothermal treatment of steel fibers improves bonding, addressing the issues of high viscosity and poor fluidity and bonding in ultra-high performance concrete.
Patent Information
- Application Number
- CN202411396053.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-08
- Publication Date
- 2024-12-20
AI Technical Summary
Ultra-high performance concrete exhibits high viscosity and poor fluidity due to low water-cement ratio and the addition of steel fibers, which also leads to insufficient bonding between the fibers and the concrete matrix, weakening mechanical strength.
A preparation process involving the use of a polycarboxylic acid water reducer and silane coupling agent to reduce viscosity and improve fluidity, combined with a hydrothermal treatment of steel fibers in a saturated lime water system containing sodium hydroxide and nano-silicon dioxide to enhance bonding.
The process effectively reduces concrete slurry viscosity, improves fluidity, and enhances the bonding between steel fibers and the concrete matrix, resulting in improved mechanical strength and construction ease.
Smart Images

Figure CN119161153A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of concrete material preparation, and in particular to a preparation process of low-viscosity, high-fluidity and ultra-high-performance concrete. Background Art
[0002] The information disclosed in this background technology section is only intended to enhance the understanding of the overall background of the invention, and should not necessarily be regarded as an admission or any form of suggestion that the information constitutes the prior art already known to a person skilled in the art.
[0003] Ultra-High Performance Concrete (UHPC) is a building material composed of cement, fine aggregate, admixtures, fiber groups, etc., which has high durability, high toughness, and high strength, namely the "three highs". Its material strength and durability have reached a level far exceeding that of traditional silicate cement, and it can resist the damage of various environmental factors such as acid and alkali erosion, freeze-thaw cycles, and chemical corrosion. As a green and environmentally friendly innovative engineering material, ultra-high performance concrete has been widely used in bridges, tunnels, buildings, marine engineering and other fields.
[0004] One of the reasons why ultra-high performance concrete has high strength is that it usually uses a low water-cement ratio of less than 0.25, which is much lower than the 0.4~0.5 of traditional concrete, thereby significantly reducing the porosity in the formed concrete structure and forming a more compact structure. However, this low water-cement ratio also causes the ultra-high performance concrete slurry to have high viscosity and poor fluidity. In addition, the steel fiber added to maintain high strength will further reduce the fluidity of the ultra-high performance concrete slurry and increase the difficulty of construction. In addition, due to the smooth surface of the steel fiber, the bonding force with the concrete matrix is insufficient, which weakens the improvement of the concrete strength by the steel fiber. Summary of the invention
[0005] In view of the above problems, the present invention provides a preparation process of ultra-high performance concrete with low viscosity and high fluidity, which not only reduces the viscosity of ultra-high performance concrete slurry and improves fluidity while maintaining a low water-cement ratio, but also improves the bonding force between steel fibers and concrete matrix. Specifically, the technical solution of the present invention is as follows.
[0006] A preparation process of low-viscosity, high-fluidity, ultra-high performance concrete, comprising the following steps: (1) Mix silicate cement powder, sand fine aggregate, silica fume and fly ash evenly, then spray polycarboxylate water reducer into the obtained mixed powder while stirring, and mix well to obtain pretreated mixed powder.
[0007] (2) spraying anhydrous ethanol solution containing a silane coupling agent into the pretreated mixed powder under stirring conditions, and drying under stirring to obtain a modified mixed powder for standby use.
[0008] (3) The surface galvanized steel fiber is placed in saturated lime water containing sodium hydroxide and nano-silicon dioxide, and then the system is subjected to a hydrothermal reaction. After completion, the fiber is separated to obtain the surface treated fiber, and the obtained liquid phase is used for later use.
[0009] (4) The modified mixed powder and the surface treated fiber are mixed evenly, and then the liquid phase is added and mixed with clean water and then mixed evenly to obtain ultra-high performance concrete.
[0010] Furthermore, in step (1), the ratio of silicate cement powder, sand fine aggregate, silica fume and fly ash is 35-52 parts by weight: 40-75 parts by weight: 10-16 parts by weight: 5-7 parts by weight.
[0011] Furthermore, in step (1), the polycarboxylic acid water-reducing agent accounts for 1.5-2.2% of the mass of the mixed powder.
[0012] Furthermore, in step (2), the ratio of the pre-treated mixed powder to the anhydrous ethanol solution is 1 g: 1-1.8 ml. The mass fraction of the silane coupling agent in the anhydrous ethanol solution is 0.7-1.1%. Optionally, the silane coupling agent includes at least one of KH550, KH560, KH570, etc.
[0013] Furthermore, in step (2), the drying temperature is 60-75° C. and the drying time is 15-30 min.
[0014] Furthermore, in step (3), the ratio of the galvanized steel fiber to saturated lime water is 1 g: 20-40 ml. Optionally, the galvanized steel fiber has a length of 10-20 mm and a diameter of 0.1-0.3 mm.
[0015] Furthermore, in step (3), the concentration of sodium hydroxide in the saturated lime water is 0.35-0.6 mol / L.
[0016] Furthermore, in step (3), the content of nano-silicon dioxide in the saturated lime water is 10-15 g / L.
[0017] Furthermore, in step (3), the temperature of the hydrothermal reaction is 180-250° C., and the time is 6-10 hours.
[0018] Furthermore, in step (4), the surface treated fiber accounts for 3-15% of the mass of the modified mixed powder.
[0019] Furthermore, in step (4), the total mass of the liquid phase and clean water is 0.17-0.23% of the mass of the silicate cement powder, wherein the liquid phase accounts for 20-30%.
[0020] Compared with the prior art, the technical solution of the present invention has at least the following beneficial effects: (1) The present invention first applies a polycarboxylic acid water reducer after mixing the various powders used to prepare high-performance concrete, and then applies an anhydrous ethanol solution containing a silane coupling agent to prepare the modified mixed powder, which effectively reduces the viscosity of the prepared concrete slurry and improves fluidity. This is because after the water reducer and the silane coupling agent are grafted on the surface of the powder particles, on the one hand, the water reducer can form a water film on the surface of the particles and reduce the effects of steric hindrance and increase the agglomeration of the powder particles, thereby improving fluidity. At the same time, the hydrophobicity of the silane coupling agent can appropriately reduce the water absorption of the particles, avoiding excessive water absorption by the powder particles, resulting in a rapid reduction of free water in the slurry and insufficient fluidity, so that the powder particles can not only use limited water to form good fluidity and low viscosity, but also keep the formed slurry in good fluidity. Furthermore, the present invention adds the alkaline liquid phase after the hydrothermal treatment of steel fibers to the mixed powder to prepare concrete slurry. After the concrete slurry containing this alkaline liquid phase catalyst is poured, the early alkaline environment provided by it can promote the hydrolysis of the silane coupling agent on the surface of the powder particles, thereby increasing the contact between the powder particles and the clean water in the concrete, so that the raw materials with hydration and gelling properties such as the silicate cement powder, silica ash and fly ash can be more fully hydrated to avoid adverse effects on mechanical properties. At the same time, the silanol groups formed by the hydrolysis of the silane coupling agent react with the hydroxyl groups on the surface of the powder particles to dehydrate and condense, which helps to bridge the powder particles and increase the strength of the concrete structure. In addition, the alkaline liquid phase can also alkali-excite silica ash and fly ash to improve their gelling activity. In addition, the liquid phase also contains nano-hydrated calcium silicate, which can play a role in inducing the formation of hydration products and promoting the hydration reaction, so that more gelling components are formed in the concrete, which helps to improve the mechanical strength of the concrete. Through the above method, the silane coupling agent plays different roles in different stages, which not only alleviates the problem of high viscosity and low fluidity of concrete slurry under low water-cement ratio, but also improves the mechanical strength of concrete.
[0021] (2) The present invention uses a saturated lime water system containing sodium hydroxide and nano-silicon dioxide to treat the surface of galvanized steel fibers by hydrothermal reaction, which effectively solves the problem of insufficient bonding between the steel fibers and the concrete matrix, thereby improving the mechanical strength of the concrete. This is because the galvanized layer on the surface of the steel fibers gradually dissolves in an alkaline environment, and the exposed surface of the steel fibers forms a passivation film on the surface of the steel fibers in an alkaline environment. The above two reactions are carried out in coordination to not only roughen the surface of the steel fibers, but also re-form a protective layer on the surface of the steel fibers, thereby improving the bonding between the steel fibers and the concrete matrix and helping to avoid the problem of strength reduction of the steel fibers due to rust. At the same time, the nano-silicon dioxide and saturated limestone form nano-hydrated calcium silicate particles during the hydrothermal reaction, a portion of which is doped into the passivation film on the surface of the steel fibers, which not only further improves the surface roughness of the steel fibers. At the same time, the nano-hydrated calcium silicate particles also help to promote the hydration reaction, promote the increase of the gelling components on the surface of the steel fibers, improve the bonding between the steel fibers and the concrete matrix, and thereby help to improve the mechanical strength of the concrete structure. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] It should be noted that the drawings in the specification, which constitute a part of the present invention, are used to provide a further understanding of the present invention and do not constitute an improper limitation of the present invention.
[0023] Figure 1 This is a sample photo of the surface treated fiber prepared in Example 1 below.
[0024] Figure 2 This is a flowability test chart of the ultra-high performance concrete prepared in the following Example 1.
[0025] Figure 3 This is a flowability test chart of the ultra-high performance concrete prepared in the following Example 2. DETAILED DESCRIPTION
[0026] The present invention will be further described below in conjunction with specific examples. It should be understood that these examples are only used to illustrate the present invention and are not intended to limit the scope of the present invention. Unless otherwise defined, all professional and scientific terms used in the present invention have the same meaning as those familiar to those skilled in the art. The preferred implementation methods and materials described in the present invention are only for demonstration purposes. The reagents or raw materials used in the present invention can be purchased through conventional channels. If there are no special instructions, the reagents or raw materials used in the present invention are used in a conventional manner in the art or are used according to the product specification. Now the technical scheme of the present invention is further described in conjunction with specific embodiments.
[0027] Example 1 A preparation process of low-viscosity, high-fluidity, ultra-high performance concrete, comprising the following steps: (1) 42.5 ordinary Portland cement powder, sand fine aggregate, silica fume and fly ash are mixed in a ratio of 40 parts by weight: 65 parts by weight: 12 parts by weight: 5.5 parts by weight and stirred evenly. Then, polycarboxylic acid water reducer is sprayed on the obtained mixed powder while stirring. The water reducer accounts for 1.8% of the mass of the mixed powder. After completion, stirring is continued for 10 minutes to obtain a pretreated mixed powder for standby use.
[0028] (2) Add silane coupling agent (KH550) to anhydrous ethanol to form a solution a with a mass fraction of 0.9%. Then spray the solution a into the pretreated mixed powder under stirring conditions, with a material-liquid ratio of 1g:1.5ml. Then dry the mixture under stirring (temperature 70°C, time 20min), and obtain a modified mixed powder for standby use.
[0029] (3) Place a surface galvanized steel fiber with a length of 14 mm and a diameter of 0.3 mm in saturated lime water containing sodium hydroxide and nano-silicon dioxide, with a material-liquid ratio of 1 g:30 ml. The sodium hydroxide concentration in the saturated lime water is 0.4 mol / L, and the nano-silicon dioxide content is 12 g / L. Then the resulting mixed system is hydrothermally reacted in a reactor at 220°C for 8.5 hours. After completion, the fiber is filtered out to obtain a surface-treated fiber (such as Figure 1 The obtained liquid phase is used for later use.
[0030] (4) The modified mixed powder and the surface treated fiber of this embodiment are mixed and stirred evenly, and the fiber accounts for 10% of the mass of the modified mixed powder. Then, the liquid phase and clean water are added, and the total mass of the two is 0.2% of the mass of the 42.5 ordinary Portland cement powder, and the liquid phase accounts for 25%. Then stir for 2 minutes to obtain ultra-high performance concrete slurry.
[0031] The fluidity of the ultra-high performance concrete slurry prepared in this embodiment was tested according to the "Method for Determining the Fluidity of Cement Mortar" (GBT2419-2005) (e.g. Figure 2 As shown). In addition, the tensile strength test of the specimen made of the ultra-high performance concrete slurry prepared in this embodiment was carried out according to the "Concrete Physical and Mechanical Properties Test Method Standard" (GB / T 50081-2019). The results are: fluidity = 233mm, 28d tensile strength = 13.07 MPa.
[0032] Example 2 A preparation process of low-viscosity, high-fluidity, ultra-high performance concrete, comprising the following steps: (1) 42.5 ordinary Portland cement powder, sand fine aggregate, silica fume and fly ash are mixed in a ratio of 52 parts by weight: 75 parts by weight: 16 parts by weight: 7 parts by weight and stirred evenly. Then, polycarboxylic acid water reducer is sprayed on the obtained mixed powder while stirring. The water reducer accounts for 2.2% of the mass of the mixed powder. After completion, stirring is continued for 15 minutes to obtain a pretreated mixed powder for standby use.
[0033] (2) Add silane coupling agent (KH560) to anhydrous ethanol to form a solution a with a mass fraction of 1.1%. Then spray the solution a into the above-mentioned pretreated mixed powder under stirring conditions, with a material-liquid ratio of 1g:1.0ml. Then dry the mixture under stirring (temperature 75°C, time 15min), and obtain a modified mixed powder for standby use.
[0034] (3) Place a surface galvanized steel fiber with a length of 10 mm and a diameter of 0.2 mm in saturated lime water containing sodium hydroxide and nano-silicon dioxide, with a solid-liquid ratio of 1 g:40 ml. The sodium hydroxide concentration in the saturated lime water is 0.35 mol / L, and the nano-silicon dioxide content is 10 g / L. Then, the resulting mixed system is hydrothermally reacted in a reactor at 250°C for 6 hours. After completion, the fiber is filtered out to obtain a surface-treated fiber, and the obtained liquid phase is used for later use.
[0035] (4) The modified mixed powder and the surface treated fiber of this embodiment are mixed and stirred evenly, and the fiber accounts for 15% of the mass of the modified mixed powder. Then, the liquid phase and clean water are added, and the total mass of the two is 0.23% of the mass of the 42.5 ordinary Portland cement powder, in which the liquid phase accounts for 20%. Then stir for 2 minutes to obtain ultra-high performance concrete slurry.
[0036] The fluidity of the ultra-high performance concrete slurry prepared in this embodiment was tested according to the "Method for Determining the Fluidity of Cement Mortar" (GBT2419-2005) (e.g. Figure 3 As shown). In addition, the tensile strength test of the specimen made of the ultra-high performance concrete slurry prepared in this embodiment was carried out according to the "Concrete Physical and Mechanical Properties Test Method Standard" (GB / T 50081-2019). The results are: fluidity = 239mm, 28d tensile strength = 12.64 MPa.
[0037] Example 3 A preparation process of low-viscosity, high-fluidity, ultra-high performance concrete, comprising the following steps: (1) 42.5 ordinary Portland cement powder, sand fine aggregate, silica fume and fly ash are mixed in a ratio of 35 parts by weight: 40 parts by weight: 10 parts by weight: 5 parts by weight and stirred evenly. Then, polycarboxylic acid water reducer is sprayed on the obtained mixed powder while stirring. The water reducer is 1.5% of the mass of the mixed powder. After completion, stirring is continued for 12 minutes to obtain a pretreated mixed powder for standby use.
[0038] (2) Add silane coupling agent (KH570) to anhydrous ethanol to form a solution a with a mass fraction of 0.7%. Then spray the solution a into the above-mentioned pretreated mixed powder under stirring conditions, with a material-liquid ratio of 1g:1.8ml. Then dry the mixture under stirring (temperature 60°C, time 30min), and obtain a modified mixed powder for standby use.
[0039] (3) Place a surface galvanized steel fiber with a length of 20 mm and a diameter of 0.1 mm in saturated lime water containing sodium hydroxide and nano-silicon dioxide, with a solid-liquid ratio of 1 g:20 ml. The sodium hydroxide concentration in the saturated lime water is 0.6 mol / L, and the nano-silicon dioxide content is 15 g / L. Then, the resulting mixed system is subjected to a hydrothermal reaction at 180°C in a reactor for 10 hours. After completion, the fiber is filtered out to obtain a surface-treated fiber, and the obtained liquid phase is used for later use.
[0040] (4) The modified mixed powder and the surface treated fiber of this embodiment are mixed and stirred evenly, and the fiber accounts for 3% of the mass of the modified mixed powder. Then, the liquid phase and clean water are added, and the total mass of the two is 0.17% of the mass of the 42.5 ordinary Portland cement powder, in which the liquid phase accounts for 30%. Then stir for 2 minutes to obtain ultra-high performance concrete slurry.
[0041] The fluidity of the ultra-high performance concrete slurry prepared in this embodiment was tested according to the "Method for Determining the Fluidity of Cement Mortar" (GBT2419-2005). In addition, the tensile strength of the specimens made of the ultra-high performance concrete slurry prepared in this embodiment was tested according to the "Standard for Test Methods for Physical and Mechanical Properties of Concrete" (GB / T50081-2019). The results are: fluidity = 228 mm, 28d tensile strength = 13.75 MPa.
[0042] Example 4 A preparation process of low-viscosity, high-fluidity, ultra-high performance concrete, comprising the following steps: (1) 42.5 ordinary Portland cement powder, sand fine aggregate, silica fume and fly ash are mixed in a ratio of 40 parts by weight: 65 parts by weight: 12 parts by weight: 5.5 parts by weight and stirred evenly. Then, polycarboxylic acid water reducer is sprayed on the obtained mixed powder while stirring. The water reducer accounts for 1.8% of the mass of the mixed powder. After completion, stirring is continued for 10 minutes to obtain a pretreated mixed powder for standby use.
[0043] (2) The pretreated mixed powder of this embodiment and the surface treated fiber prepared in the above embodiment 1 are mixed and stirred evenly, and the fiber accounts for 10% of the mass of the modified mixed powder. Then, the liquid phase and clean water are added, and the total mass of the two is 0.2% of the mass of the 42.5 ordinary Portland cement powder, in which the liquid phase accounts for 25%. Then, stir for 2 minutes to obtain ultra-high performance concrete slurry.
[0044] The fluidity of the ultra-high performance concrete slurry prepared in this embodiment was tested according to the "Method for Determining the Fluidity of Cement Mortar" (GBT2419-2005). In addition, the tensile strength of the specimens made of the ultra-high performance concrete slurry prepared in this embodiment was tested according to the "Standard for Test Methods for Physical and Mechanical Properties of Concrete" (GB / T50081-2019). The results are: fluidity = 211 mm, 28d tensile strength = 12.14 MPa.
[0045] Example 5 A preparation process of low-viscosity, high-fluidity, ultra-high performance concrete, comprising the following steps: (1) Mix 42.5 parts of ordinary Portland cement powder, sand fine aggregate, silica fume and fly ash in a ratio of 40 parts by weight: 65 parts by weight: 12 parts by weight: 5.5 parts by weight, stir evenly, and obtain a mixed powder for use.
[0046] (2) Add silane coupling agent (KH550) to anhydrous ethanol to form a solution a with a mass fraction of 0.9%. Then spray the solution a into the mixed powder of step (1) under stirring, with a material-liquid ratio of 1 g:1.5 ml. Then dry the mixture under stirring (temperature 70°C, time 20 min), and obtain a modified mixed powder for standby use.
[0047] (3) The modified mixed powder of this embodiment and the surface treated fiber prepared according to the method of the above embodiment 1 are mixed and stirred evenly, and the fiber accounts for 10% of the mass of the modified mixed powder. Then, the liquid phase and clean water are added, and the total mass of the two is 0.2% of the mass of the 42.5 ordinary Portland cement powder, in which the liquid phase accounts for 25%. Then, stir for 2 minutes to obtain ultra-high performance concrete slurry.
[0048] The fluidity of the ultra-high performance concrete slurry prepared in this embodiment was tested according to the "Method for Determining the Fluidity of Cement Mortar" (GBT2419-2005). In addition, the tensile strength of the specimens made of the ultra-high performance concrete slurry prepared in this embodiment was tested according to the "Standard for Test Methods for Physical and Mechanical Properties of Concrete" (GB / T50081-2019). The results are: fluidity = 194mm, 28d tensile strength = 12.71MPa.
[0049] Example 6 A preparation process of ultra-high performance concrete with low viscosity and high fluidity is the same as the above-mentioned embodiment 2, except that step (4) of this embodiment adopts the following method: the modified mixed powder and the surface treated fiber are mixed and stirred evenly, and the fiber accounts for 15% of the mass of the modified mixed powder. Then, 0.23% of the mass of the 42.5 ordinary silicate cement powder is added and stirred for 2 minutes to obtain ultra-high performance concrete slurry.
[0050] The fluidity of the ultra-high performance concrete slurry prepared in this embodiment was tested according to the "Method for Determining the Fluidity of Cement Mortar" (GBT2419-2005). In addition, the tensile strength of the specimens made of the ultra-high performance concrete slurry prepared in this embodiment was tested according to the "Standard for Test Methods for Physical and Mechanical Properties of Concrete" (GB / T50081-2019). The results are: fluidity = 235 mm, 28d tensile strength = 11.04 MPa.
[0051] Example 7 A preparation process of low-viscosity, high-fluidity, ultra-high performance concrete, comprising the following steps: (1) Place a surface galvanized steel fiber with a length of 20 mm and a diameter of 0.1 mm in saturated lime water containing nano-silicon dioxide (content of 15 g / L), with the solid-liquid ratio of 1 g:20 ml. Then, the resulting mixed system is subjected to hydrothermal reaction at 180 ° C in a reactor for 10 hours. After completion, the fiber is filtered out to obtain the surface-treated fiber, and the obtained liquid phase is used for later use.
[0052] (2) The modified mixed powder prepared according to the method of the above-mentioned Example 3 and the surface-treated fiber of this example are mixed and stirred evenly, and the fiber accounts for 3% of the mass of the modified mixed powder. Then, clean water and the liquid phase of this example are added, and the total mass of the two is 0.17% of the mass of the 42.5 ordinary Portland cement powder, and the liquid phase accounts for 30%. Then, stir for 2 minutes to obtain ultra-high performance concrete slurry.
[0053] The fluidity of the ultra-high performance concrete slurry prepared in this embodiment was tested according to the "Method for Determining the Fluidity of Cement Mortar" (GBT2419-2005). In addition, the tensile strength of the specimens made of the ultra-high performance concrete slurry prepared in this embodiment was tested according to the "Standard for Test Methods for Physical and Mechanical Properties of Concrete" (GB / T50081-2019). The results are: fluidity = 224mm, 28d tensile strength = 10.57MPa.
[0054] Example 8 A preparation process of low-viscosity, high-fluidity, ultra-high performance concrete, comprising the following steps: (1) Place a surface galvanized steel fiber with a length of 10 mm and a diameter of 0.2 mm in saturated lime water containing sodium hydroxide, with a material-liquid ratio of 1 g:40 ml. The concentration of sodium hydroxide in the saturated lime water is 0.35 mol / L. Then, the resulting mixed system is subjected to a hydrothermal reaction at 250° C. in a reactor for 6 hours. After completion, the fiber is filtered out to obtain a surface-treated fiber, and the obtained liquid phase is used for later use.
[0055] (2) The modified mixed powder prepared according to the method of Example 2 and the surface-treated fiber of this example are mixed and stirred evenly, and the fiber accounts for 15% of the mass of the modified mixed powder. Then, the liquid phase and clean water of this example are added, and the total mass of the two is 0.23% of the mass of the 42.5 ordinary Portland cement powder, in which the liquid phase accounts for 20%. Then, stir for 2 minutes to obtain ultra-high performance concrete slurry.
[0056] The fluidity of the ultra-high performance concrete slurry prepared in this embodiment was tested according to the "Method for Determining the Fluidity of Cement Mortar" (GBT2419-2005). In addition, the tensile strength of the specimens made of the ultra-high performance concrete slurry prepared in this embodiment was tested according to the "Standard for Test Methods for Physical and Mechanical Properties of Concrete" (GB / T50081-2019). The results are: fluidity = 237 mm, 28d tensile strength = 11.23 MPa.
[0057] Example 9 A preparation process of low-viscosity, high-fluidity, ultra-high performance concrete, comprising the following steps: (1) A steel fiber with a length of 20 mm and a diameter of 0.1 mm is placed in saturated lime water containing sodium hydroxide and nano-silicon dioxide, with a material-liquid ratio of 1 g:20 ml. The sodium hydroxide concentration in the saturated lime water is 0.6 mol / L, and the nano-silicon dioxide content is 15 g / L. The resulting mixed system is then subjected to a hydrothermal reaction at 180°C in a reactor for 10 hours. After completion, the fiber is filtered out to obtain a surface-treated fiber, and the obtained liquid phase is used for later use.
[0058] (2) The modified mixed powder prepared according to the method of the above-mentioned Example 3 and the surface-treated fiber of this example are mixed and stirred evenly, and the fiber accounts for 3% of the mass of the modified mixed powder. Then, clean water and the liquid phase of this example are added, and the total mass of the two is 0.17% of the mass of the 42.5 ordinary Portland cement powder, and the liquid phase accounts for 30%. Then, stir for 2 minutes to obtain ultra-high performance concrete slurry.
[0059] The fluidity of the ultra-high performance concrete slurry prepared in this embodiment was tested according to the "Method for Determining the Fluidity of Cement Mortar" (GBT2419-2005). In addition, the tensile strength of the specimens made of the ultra-high performance concrete slurry prepared in this embodiment was tested according to the "Standard for Test Methods for Physical and Mechanical Properties of Concrete" (GB / T50081-2019). The results are: fluidity = 230 mm, 28d tensile strength = 10.82 MPa.
[0060] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention is described in detail with reference to the above embodiments, those skilled in the art can still modify the technical solutions described in the above embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made shall be included in the protection scope of the present invention.
Claims
1. A process for preparing low-viscosity, high-fluidity, ultra-high performance concrete, characterized in that: The steps include: (1) Mixing silicate cement powder, sand fine aggregate, silica fume and fly ash evenly, and then spraying polycarboxylate water reducer into the obtained mixed powder while stirring, and mixing to obtain a pretreated mixed powder; (2) spraying anhydrous ethanol solution containing a silane coupling agent into the pretreated mixed powder under stirring conditions, and drying under stirring after completion to obtain a modified mixed powder for standby use; (3) placing the surface galvanized steel fiber in saturated lime water containing sodium hydroxide and nano-silicon dioxide, and then subjecting the system to a hydrothermal reaction. After completion, the fiber is separated to obtain the surface treated fiber, and the obtained liquid phase is used for later use; (4) The modified mixed powder and the surface treated fiber are mixed evenly, and then the liquid phase is added and mixed with clean water and then mixed evenly to obtain ultra-high performance concrete.
2. The process for preparing low-viscosity, high-fluidity, ultra-high performance concrete according to claim 1, characterized in that: In step (1), the ratio of silicate cement powder, sand fine aggregate, silica fume and fly ash is 35-52 parts by weight: 40-75 parts by weight: 10-16 parts by weight: 5-7 parts by weight.
3. The process for preparing low-viscosity, high-fluidity, ultra-high performance concrete according to claim 1, characterized in that: In step (1), the polycarboxylate water reducer is 1.5-2.2% of the mass of the mixed powder.
4. The process for preparing low-viscosity, high-fluidity, ultra-high performance concrete according to claim 1, characterized in that: In step (2), the ratio of the pretreated mixed powder to the anhydrous ethanol solution is 1 g: 1-1.8 ml; the mass fraction of the silane coupling agent in the anhydrous ethanol solution is 0.7-1.1%; Optionally, in step (2), the silane coupling agent includes at least one of KH550, KH560, and KH570; Optionally, in step (2), the drying temperature is 60-75° C. and the drying time is 15-30 min.
5. The process for preparing low-viscosity, high-fluidity, ultra-high performance concrete according to claim 1, characterized in that: In step (3), the ratio of the galvanized steel fiber to saturated lime water is 1 g: 20-40 ml; Optionally, in step (3), the galvanized steel fiber has a length of 10-20 mm and a diameter of 0.1-0.3 mm.
6. The process for preparing low-viscosity, high-fluidity, ultra-high performance concrete according to claim 1, characterized in that: In step (3), the concentration of sodium hydroxide in the saturated lime water is 0.35-0.6 mol / L.
7. The process for preparing low-viscosity, high-fluidity, ultra-high performance concrete according to claim 1, characterized in that: In step (3), the content of nano-silicon dioxide in the saturated lime water is 10-15 g / L.
8. The process for preparing low-viscosity, high-fluidity, ultra-high performance concrete according to claim 1, characterized in that: In step (3), the temperature of the hydrothermal reaction is 180-250° C. and the time is 6-10 hours.
9. The process for preparing low-viscosity, high-fluidity, ultra-high performance concrete according to any one of claims 1 to 8, characterized in that: In step (4), the surface treated fiber accounts for 3-15% of the mass of the modified mixed powder.
10. The process for preparing low-viscosity, high-fluidity, ultra-high performance concrete according to any one of claims 1 to 8, characterized in that: In step (4), the total mass of the liquid phase and clean water is 0.17-0.23% of the mass of the silicate cement powder, of which the liquid phase accounts for 20-30%.
